Dinghai fusheng records. 3 - Feitianyexiang (Fei Tian Ye Xiang. Dinghai Fusheng Records, 2025)
"The bustling capital of the southern Jin Empire, Jiankang, offers the illusion of safety--but for Chen Xing and Xiang Shu, it may hold more danger than they bargained for. The Demon God Chiyou's influence has already reached the south, and his forces are gathering. To end the Silence of All Magic, they must uncover the truth behind the mythical Dinghai Pearl. But the deeper they dig, the more Xiang Shu discovers an impossible connection between the Pearl's long-lost creator and his own past. With the world's magic gone, Chen Xing's Heart Lamp is the only light that can hold back the darkness. But every time he uses it, it drains his life force--leaving him weaker, and the toll growing with each battle. Chen Xing is ready to make that sacrifice but Xiang Shu is not willing to let him"--Back cover.